Keefektifan Pembelajaran Project Based Learning Untuk Meningkatkan Manajemen Waktu Belajar Siswa - Nur Isna; Veny Iswantiningtyas; Anisyah Anisyah (Jurnal Pendidikan Sosial Dan Konseling, 2025)
In adolescence, there are often problems with time management difficulties because they do not have an understanding of time management. Students' inability to manage time can have a negative impact on students, namely a lot of wasted time. This study aims to determine the effectiveness of Project Based Learning to improve high school students' study time management. The purpose of this study is to find out. Implementation of Project Based Learning to improve study time management of class XI-12 students at SMAN 2 Kediri. This study uses the guidance and counseling action research method with a popularity of 36 students carried out in the pre-cycle and two cycles with pretest-posttest. The results showed a significant increase in students' study time management from 75% in the pre-cycle, 80% in the first cycle and 86% in the second cycle. So it can be concluded that the project-based learning strategy is effective in improving study time management in class XI-12 students of SMAN 2 Kediri.